Effect of twitter investor engagement on cryptocurrencies during the COVID-19 pandemic - Bouteska, Ahmed; Hájek, Petr; Abedin, Mohammad Zoynul; Dong, Yizhe (Elsevier Science BV, 2023)
This study aims to examine whether the prices and returns of two cryptocurrencies, Dogecoin and Ethereum, are affected by Twitter engagement following the COVID-19 pandemic. We use the autoregressive integrated moving average with explanatory variables model to integrate the effects of investor attention and engagement on Dogecoin and Ethereum returns using data from December 31, 2020, to May 12, 2021. The results provide evidence supporting the hypothesis of a strong effect of Twitter investor engagement on Dogecoin returns; however, no potential impact is identified for Ethereum. These findings add to the growing evidence regarding the effect of social media on the cryptocurrency market and have useful implications for investors and corporate investment managers concerning investment decisions and trading strategies.
Vliv zapojení investorů na twitteru na kryptoměny během pandemie COVID-19
Keywords: Twitter; Investor engagement; Dogecoin; Ethereum; ARIMAX; COVID-19; Twitter; Zapojení investorů; Dogecoin; Ethereum; ARIMAX; COVID-19